2021
DOI: 10.1186/s12870-021-03355-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of PME genes, evolution and expression analyses in soybean (Glycine max L.)

Abstract: Background Pectin methylesterase (PME) is one of pectin-modifying enzyme that affects the pectin homeostasis in cell wall and regulates plant growth and diverse biological processes. The PME genes have been well explored and characterized in different plants. Nevertheless, systematic research on the soybean (Glycine max L.) PME genes remain lacking. Results We identified 127 Glycine max PME genes (GmPME) from the soybean Wm82.a2.v1 genome, which un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Some studies have shown that the expansion of plant gene families is mainly facilitated by segmental and tandem duplication events [27,28]. Segmental duplication frequently occurs during polyploidization and chromosomal rearrangements, resulting in the presence of repeated chromosomal blocks in the genome; tandem duplications are clusters of multiple adjacent homologous gene family members (two or more members) on a chromosome [29].…”
Section: Chromosomal Location Of Ntftsh Gene and Gene Segment Duplica...mentioning
confidence: 99%
“…Some studies have shown that the expansion of plant gene families is mainly facilitated by segmental and tandem duplication events [27,28]. Segmental duplication frequently occurs during polyploidization and chromosomal rearrangements, resulting in the presence of repeated chromosomal blocks in the genome; tandem duplications are clusters of multiple adjacent homologous gene family members (two or more members) on a chromosome [29].…”
Section: Chromosomal Location Of Ntftsh Gene and Gene Segment Duplica...mentioning
confidence: 99%
“…The red and dark purple boxes denote high levels of expression and low levels of expression, respectively. LF, leaf; RT, root; ST, stem; FW, flower; MGF, mature green fruit; FCF, full-colored fruit Sénéchal et al 2014b;Wang et al 2021). In this study, we identified 48 PME genes from the sweet orange genome (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Plenty of PME genes in many plant species are dominantly expressed in whole flowers or specific floral tissues such as anthers, pollen, pollen grains, pollen tubes or corn silk (Kim et al 2010;Kim et al 2015;Louvet et al 2006;Moran Lauter et al 2017;Wang et al 2021;Wen et al 2020;Zhang et al 2019), indicating that they have a specific biological function in reproductive development. Arabidopsis QUARTET1 (QRT1, AT5G55590), which encodes a PME isoform, plays a key role in the separation of pollen grains from pollen tetrads after microsporogenesis in the pollen mother cell (Francis et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the protein structures, Type-I PME and Type-II PME proteins share the PME domains, and Type-I PME proteins also contains the PRO-region, an additional N-terminal region similar to the PMEI domain [9]. Recently, PME genes have been discovered in various plant species, such as 66 PME genes, which were identified from Arabidopsis thaliana [10], 53 from Citrus sinensis [11], 61 from Glycine max [12], 54 from Fragaria vesca [12], and 56 from Solanum tuberosum [13]. The PME genes are tightly linked to various functions of plants, such as fruit maturity and softening [14,15], seed germination and development [16], pollen development [17,18], stem elongation [19], root hair formation [19], and stress response [20,21].…”
Section: Introductionmentioning
confidence: 99%